Dietary Patterns, Energy Intake, and Hemoglobin Levels with Nutritional Status Nutrition Students - Estu Ayu Ningsih; Sugeng Eko Irianto; Bambang Setiaji; Endang Budiati; Dian Utama Pratiwi Putri (Jurnal Ilmiah Kesehatan (JIKA), 2026)
Nutritional status is an important indicator of students’ health and productivity, particularly among nutrition students who are expected to have a good understanding of dietary patterns. This study aimed to determine the relationship between eating behavior, energy intake, and hemoglobin levels with nutritional status.This study used a quantitative approach with a cross-sectional design. The population consisted of 406 students from the Nutrition Department of Poltekkes Kemenkes Tanjungkarang, with a sample of 100 subjects selected using proportionate stratified random sampling. Data were collected using the DEBQ (Dutch Eating Behaviour Questionnaire) to assess eating behavior, a 2×24-hour dietary recall to measure energy intake, and hemoglobin level measurement using the finger prick method. Data were analyzed using Chi-square and multiple logistic regression. The multivariate model was statistically significant (p < 0.001, Nagelkerke R Square = 0.314 ). Energy intake and hemoglobin levels were significantly associated with nutritional status, where inadequate energy intake showed a higher prevalence ratio (PR) for abnormal nutritional status. Meanwhile, eating behavior was not a significant factor. The results showed that energy intake and hemoglobin levels were significantly associated with nutritional status. Students with inadequate energy intake were more likely to have abnormal nutritional status. Meanwhile, eating behavior was not significantly associated with nutritional status. Based on these findings, students are encouraged to improve emotional eating control and maintain balanced energy intake according to their nutritional needs to achieve optimal nutritional status.